Brewing with green malt for an energy and water efficient process: challenges and opportunities - Dugulin, Celina Angela (2021)
The malting process can be separated into three key steps: steeping, germination and kilning – the latter being the most energy intensive step accounting for ~78% of the total energy demand. Naturally, the kilning process becomes the main point of interest to reduce the maltings energy footprint. Furthermore, malting and brewing involve sequential wetting and drying steps. Viewed solely from an energy and water use perspective these processes make little sense. Brewing beer using ‘green’ (germinated, but not dried) malt, could be a solution to making the malting industry more energy and water efficient. Such a process would reduce substantial energy input associated with kilning and conserve the water contained in the green malt. However, brewing with undried malt represents very disruptive technology and multiple aspects need to be considered to successfully brew with this ‘novel’ grist material (Dugulin et al. 2021; doi: 10.1080/03610470.2021.1902710). The overall aim of this project was to demonstrate the feasibility of brewing with green malt and propose solutions to some perceived technical and biochemical (flavour) barriers.